Heritability of nervous system tumors: a sibling-based design - Tettamanti, Giorgio; Kuja-Halkola, Ralf; Lavebratt, Catharina; Talbäck, Mats; Viktorin, Alexander; Scheurer, Michael E.; Feychting, Maria; Adel Fahmideh, Maral (Frontiers in Oncology, 2024)
The previous pan-cancer, family-based quantitative genetic studies, by using a traditional twindesign, were not able to assess the heritability of nervous system tumors, due to lack of statistical power. This study, by employing a sibling-based design and using quantitative genetic modelling and hence with inherent larger power, estimated the heritability of nervous system tumors. Thus, it fills the major gap in the knowledge of proportion of the risk of these significant malignancies which is attributable to the inherited genetic and environmental factors.